NITROGEN AND BACTERIA TREATMENT EFFICIENCY OF ONSITE WASTEWATER SYSTEMS IN THE PIEDMONT OF NORTH CAROLINA - Jernigan, Jordan (East Carolina University, 2023)
Onsite wastewater treatment systems (OWTSs) are commonly used in rural areas for wastewater disposal. These systems can contribute elevated concentrations of nutrients and bacteria into water resources, resulting in potential impairment. Drinking water wells are often permitted on the same lot as OWTSs, where access to public water supply is limited. Groundwater, drinking water wells, and recreational waters containing excess nutrients and bacteria pose harmful effects on both environmental and public health. More specifically, exposure to nitrate via drinking water can lead to human health effects, such as methemoglobinemia, cancers, and pregnancy complications, and environmental health effects, such as eutrophication, algal blooms, and fish kills in surface waters. E. coli in drinking water and body contact exposure during recreational activities can lead to gastrointestinal illnesses, and in severe cases, death. The goal of this study was to evaluate OWTS treatment efficiency of nitrogen and E. coli from wastewater to groundwater in conventional- and alternative-style OWTS within an impaired watershed, Falls Lake Watershed, North Carolina, USA. Specific objectives included: 1) quantifying nitrogen and E. coli concentrations in wastewater, groundwater, and sand filter effluent; 2) determining treatment efficiencies of nitrogen and E. coli in different OWTSs; 3) assessing mechanisms of nitrogen and E. coli concentration reductions in subsoil beneath the drainfields and in a sand filter system; and 4) providing management strategies to help reduce nitrogen and E. coli inputs into impaired watersheds. Five volunteered sites (Sites 100 -- 500) with conventional- or alternative-style OWTSs were evaluated during this study. The original system age across all sites ranged from 49 -- 53 years. Replacement systems were installed at Sites 200, 400, and 500 with age since replacement ranging from 2 -- 14 years. There were three conventional-style OWTSs (e.g., gravel and chamber) and two alternative-style OWTSs (e.g., bed and single-pass sand filter). Wastewater samples were collected from septic tanks at each site and a drainfield port at Site 400. Groundwater monitoring piezometers were installed beneath the drainfields at Sites 100 -- 400. Additional piezometers were installed downgradient from the OWTSs at Sites 100 and 200. The OWTS at Site 500 was a single-pass sand filter where effluent was collected from a surface discharge pipe. Physicochemical properties (e.g., pH, dissolved oxygen, specific conductance, temperature, oxidation-reduction potential) of wastewater, groundwater, and sand filter effluent were measured in the field. Collected samples were analyzed for nitrogen species, E. coli, and chloride concentrations. Nitrate isotope analysis of groundwater was also carried out. Soil samples were collected from beneath the drainfield and analyzed for physicochemical properties (e.g., pH, effective cation exchange capacity, and sand/silt/clay percentages). The duration of the study was from September 2020 -- June 2021. Sampling occurred 4 -- 6 times at each site and at least once during each season. Specific sampling dates included September 21, 2020; November 17, 2020; January 14, 2021; March 10, 2021; April 19, 2021; and June 29, 2021. Sampling did occur during the coronavirus disease 2019 (COVID-19) pandemic, which resulted in more people working from home leading to the potential of greater residential water use and wastewater generation. Findings from this study show that OWTSs were influencing nitrogen and E. coli concentrations in groundwater and sand filter effluent. Treatment efficiency of nitrogen from wastewater to groundwater beneath the drainfields and downgradient ranged from 86 -- 89%, which performed better than the sand filter OWTS (79%). The difference in mean nitrogen concentration reductions from wastewater (~ 77 mg·L ̄¹) to groundwater and sand filter effluent (~ 11 mg·L ̄¹) was statistically significant (p < 0.01). While groundwater beneath OWTS drainfields is typically not used for drinking water, findings from this study show average nitrogen concentration in groundwater exceeds the United States Environmental Protection Agency drinking water standard of 10 mg·L ̄¹. Elevated nitrogen concentrations in groundwater can pose concerns for nearby surface waters during recharge and from surface discharging OWTSs, or if contamination occurs in drinking water wells. E. coli treatment efficiency from wastewater (median: 1,579,500 MPN·100 mL ̄¹) to groundwater and sand filter effluent (median: 7 MPN·100 mL ̄¹) was > 99% and differences in median E. coli concentrations were found to be statistically significant (p < 0.05). Any amount of E. coli in groundwater poses risks for environmental and public health due to potential exposure through drinking water contamination and/or during recreational activities. OWTSs across all sites were influencing nitrogen and E. coli concentrations in groundwater. While limited research has been conducted in the Piedmont of North Carolina regarding OWTS contributions of nitrogen and E. coli into impaired watersheds, this study suggests the need for additional research to assess how aging systems may be influencing water quality. There should be more economically affordable options for repairs of malfunctioning OWTS or cost-share programs to help cover the costs.
Keywords: Groundwater; nutrient; ESCHERICHIA COLI; septic system; sand filter; bed system; Wastewater; Nitrogen; North Carolina; Bacteria; Waste Disposal, Fluid